2015
DOI: 10.1016/j.bcmd.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with docosahexanoic acid (DHA) increases red blood cell membrane flexibility in mice with sickle cell disease

Abstract: Humans and mice with sickle cell disease (SCD) have rigid red blood cells (RBCs). Omega-3 fatty acids, such as docosahexanoic acid (DHA), may influence RBC deformability via incorporation into the RBC membrane. In this study, sickle cell (SS) mice were fed natural ingredient rodent diets supplemented with 3% DHA (DHA diet) or a control diet matched in total fat (CTRL diet). After 8 weeks of feeding, we examined the RBCs for: 1) stiffness, as measured by atomic force microscopy; 2) deformability, as measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…These findings indicated the important role of fatty acid abnormality in the chronic inflammatory state associated with the disease [14,15]. In addition, our group and others have shown that supplementing SCD patients with omega-3 fatty acids corrects cell membrane abnormalities and confer protection against vaso-occlusive pain episodes, severe anaemia and oxidative stress [16][17][18][19], and improves red blood cells flexibility in mice [20]. However, little is known about the potential antiinflammatory role of n−3 fatty acids in SCD.…”
Section: Introductionmentioning
confidence: 53%
“…These findings indicated the important role of fatty acid abnormality in the chronic inflammatory state associated with the disease [14,15]. In addition, our group and others have shown that supplementing SCD patients with omega-3 fatty acids corrects cell membrane abnormalities and confer protection against vaso-occlusive pain episodes, severe anaemia and oxidative stress [16][17][18][19], and improves red blood cells flexibility in mice [20]. However, little is known about the potential antiinflammatory role of n−3 fatty acids in SCD.…”
Section: Introductionmentioning
confidence: 53%
“…Interestingly, v-3 fatty acids are considered to be a multitarget intervention; in addition to having an antioxidative effect, they have been shown to inhibit platelet activation and blood-cell aggregation and inflammation and improve cell-membrane deformability. 65,[79][80][81][82] However, further confirmation of its efficacy on clinical outcomes is needed. The fact that 2 new phase 3 multicenter studies are expected to start enrollment soon therefore offers hope (registered at www.clinicaltrials.gov as #NCT02604368 and #NCT02525107).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent important study, Wandersee et al 93 is trying to investigate the therapeutic potential of ω-3 fatty acids for patients with homozygous sickle cell disease in a randomised, placebo-controlled, double-blind trial. Preliminary results indicate that supplementation with ω-3 fatty acids may improve inflammation and blood cell adhesion in patients with SCD.…”
Section: ω-3 Treatmentmentioning
confidence: 99%